Profile of High School Students' Numeration Literacy Abilities Using Formative Websites on Straight Movement Materials - Novita, Vernanda Dela; Permatasari, Indhah; Ekawati, Elvin Yusliana (Universitas Muhammadiyah Makassar, 2026)
This study addresses the continuing urgency to strengthen students’ numeracy literacy, a core competence needed to interpret quantitative information and solve contextual problems in physics learning. It aims to profile high school students’ numeracy literacy abilities on static material using a technology-supported formative assessment. A quantitative descriptive design was employed with 51 students from a senior high school in Surakarta selected through purposive sampling. Data were collected using a 30-item context-based numeracy literacy test administered via the Formative website and scored dichotomously, then analyzed using Rasch modelling with the QUEST program to obtain person-ability estimates and classify students into high, medium, and low categories. The results show that students’ numeracy literacy levels were distributed across the Medium (51%) and High (49%) categories, with no students in the Low category. Indicator-level findings reveal the strongest performance in interpreting quantitative information and representations (Indicator 1). At the same time, higher-level attainment was limited in applying numerical operations and formulas (Indicator 2), where no responses reached the Advanced category, and contextual reasoning (Indicator 3), which was dominated by Basic–Proficient levels. The novelty of this study lies in providing a Rasch-based diagnostic profile of numeracy literacy, specifically in straight motion, using an online formative assessment platform, yielding detailed evidence across indicators that can inform targeted instructional support. In conclusion, students demonstrated adequate numeracy literacy in straight motion overall, but improvements are needed in procedural fluency and contextual reasoning. This study contributes to physics education by demonstrating an efficient approach to diagnosing numeracy-related learning needs and supporting data-driven planning for physics instruction and assessment.